Implementasi Pengabdian Masyarakat sebagai Juri Porseni Madrasah Aliyah bidang Desain Grafis - Arin Yuli Astuti; Sugianti Sugianti; Rifqi Rahmatika Az-Zahra (Borneo Research and Education Center, 2025)
The Sports and Arts Week (Porseni) for Madrasah Aliyah (MA) level in Ponorogo is a biennial event organized by the Ministry of Religious Affairs of Ponorogo Regency to explore and develop students’ talents and creativity in sports and the arts. One of the increasingly popular and evolving competition categories is Graphic Design, which involves the use of visual elements such as typography, illustrations, and color to effectively convey messages. In 2025, MAN 1 Ponorogo was appointed as the host for the district-level Graphic Design competition. This event aims to enhance students’ skills and competitiveness in visual design, while upholding values of sportsmanship and objectivity. However, previous Porseni events have faced challenges related to the evaluation process, including a lack of transparency, subjective judgments, and a mismatch between judges’ backgrounds and the competition field. These issues have led to distrust among participants regarding the final results. To address this, the Porseni committee at MAN 1 Ponorogo has collaborated with lecturers from the Informatics Engineering department who have expertise in graphic design to serve as competition judges. This collaboration is expected to establish a more objective and fair assessment system, aligned with graphic design evaluation criteria, and ultimately improve the quality and integrity of Porseni as a whole.